The Effect of SQ3R (Survey, Question, Read, Recite, Review) to Cognitive Level of Middle School Students in Sukabumi - Yudi Setiawan (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2020)
This study aims to obtain an empirical evidence about the study of the effect of applying the SQ3R learning method (Survey, Question, Read, Recite, Review) on junior high school student learning outcomes. The method used in this study is a quasi-experimental research design, the control group pretest posttest design. The population in this study were students of class VIII SMP Negeri 9 Sukabumi, using nonrandom samples with purposive sampling technique. One class gets learning with the SQ3R (Survey, Question, Read, Recite, Review) method as an experimental class, and one class gets learning using the direct instruction model. The results of this study indicate that the SQ3R learning method significantly affects student learning outcomes. The difference in the average score of learning outcomes shows that there is an influence on student learning outcomes in each learning indicator and each cognitive level. In conclusion, SQ3R learning affects the learning outcomes of SMP VIII students at SMPN 9 Sukabumi City on pest and plant disease material.